Performance Measurement in Healthcare Incentive Plans - Antti Kauhanen; Julia Salmi; Paulus Torkki (The Research Institute of the Finnish Economy (ETLA), 2013)
By using quantitative survey data and conducting a case study, we examine performance measurement of incentive plans in Finnish private sector health care organizations. We find that the performance measures used in the incentive plans are in line with recent economic theories of performance measurement. The findings from the case study emphasize the importance of choosing appropriate performance measures and designing the pay package as a whole. Inadequate performance measurement leads to incentive plans that do not help organizations reach their goals.
Keywords: 330